“Fast” food for thought? Exploring the not-so-easy-to-digest language of Albanian newspapers - Qafzezi, Eriola (Revue internationale Animation, territoires et pratiques socioculturelles / International Journal of Sociocultural community development and practices / Revista internacional Animación, territorios y prácticas socioculturales, 2024)
Pressured to increase their market share and capture more people’s attention, newspapers are under influence. The search for sensationalist exclusivity leads to uniformity and rudeness. For the purpose of this article, several Albanian newspapers were examined in order to find out how the news are produced or « constructed ». We found a tendency to hide rather than publicize news, offering selected and readymade news that require little effort of hindsight and analysis. This dynamic reveals the deterioration of the conditions of access of the public to information allowing to question the politico-media news. The text ends with a call to reconnect with the journalistic ideal.